2019
DOI: 10.1111/cas.14113
|View full text |Cite
|
Sign up to set email alerts
|

The immune response‐related mutational signatures and driver genes in non‐small‐cell lung cancer

Abstract: Immune checkpoint blockade (ICB) therapy has achieved remarkable clinical benefit in non‐small‐cell lung cancer (NSCLC), but our understanding of biomarkers that predict the response to ICB remain obscure. Here we integrated somatic mutational profile and clinicopathologic information from 113 NSCLC patients treated by ICB (CTLA‐4/PD‐1). High tumor mutation burden (TMB) and neoantigen burden were identified significantly associated with improved efficacy in NSCLC immunotherapy. Furthermore, we identified apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 49 publications
5
70
0
1
Order By: Relevance
“…34 There is evidence that the APOBEC mutational signature is a potential predictive marker for PD-1 immunotherapy response in NSCLC. 13,35 In our genomic meta-analysis, we identified that signature 1 was associated with shortened survival time in patients with TNBC and suggested a significant association with tumor escape from immunological surveillance. A recent study indicated that short-term chemotherapy (e.g., doxorubicin and cisplatin) may induce a more favorable tumor microenvironment and increase the likelihood of response to PD-1 blockade in TNBC.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…34 There is evidence that the APOBEC mutational signature is a potential predictive marker for PD-1 immunotherapy response in NSCLC. 13,35 In our genomic meta-analysis, we identified that signature 1 was associated with shortened survival time in patients with TNBC and suggested a significant association with tumor escape from immunological surveillance. A recent study indicated that short-term chemotherapy (e.g., doxorubicin and cisplatin) may induce a more favorable tumor microenvironment and increase the likelihood of response to PD-1 blockade in TNBC.…”
Section: Discussionmentioning
confidence: 94%
“…The ligand-binding chain (alpha) of the gamma interferon receptor encoding gene IFNGR1, acted in IFNγ pathways, and its mutation was reported to regulate the immune response to PD-1 treatment. 13,32 Mutations patterns of signature 1 were commonly found in most cancer types (BRCA, LUAD, PRAD, etc. ), known as clock-like mutational process properties, which showed a correlation between the number of mutations and age at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple reviews describe barriers to successful clinical application of CAR T-cell therapy, other T-cell-based therapies, and CIs [21][22][23]. The key mechanisms of tumor immunoevasion include: (1) impaired molecular trafficking into the tumor (caused by pro-tumoral endothelium [24,25], altered chemokine profile [26][27][28], and stiff stroma [29]); (2) microenvironment-mediated alterations that include hyperacidity and increased potassium level [30], presence of myeloid derived suppressor cells (MDSCs) [31,32], tumor-associated macrophages (TAMs) [33], and their cytokines/chemokines; and (3) modulation of tumor-specific molecular pathways [34], e.g., phosphatase and tensin homolog (PTEN)/phosphoinositide 3-kinase (PI3K) [35][36][37], Janus kinase 1 (JAK1)/2 [38][39][40], isocitrate dehydrogenase (IDH) [41,42], interferon-gamma (IFNγ) and tumor necrosis factor alpha (TNFα) [43], and microRNAs and exosomes [44].…”
Section: Solid Tumors Are Prominently Heterogeneous-one Approach Doesmentioning
confidence: 99%
“…Huang et al reported that the oncolytic adenovirus carrying the SIRPα-IgG1 Fc fusion gene could block CD47 signaling in ovarian cancer cells, therefore, increasing macrophage in ltration and killing ovarian cancer cells [8] . In addition, the total mutational burden (TMB) was also correlated with cancer prognoses and affected immune responses in the tumor microenvironment [9] .…”
Section: Introductionmentioning
confidence: 99%